Strategies of Muslim Countries in Preventing a Global Recession: Case Studies of OIC Countries - Hasan, Zulfikar (UI Scholars Hub, 2024)
This study provides an overview of the global recession that has occurred the world. All countries, including developed countries, have had a significant impact on this recession. OIC countries are also inseparable from the negative effects of this recession. Almost all OIC (Organisation of Islamic Cooperation) countries have been affected by this problem. The research was conducted using descriptive qualitative research, which helps to analyze the issues discussed. The study's results have been analyzed, and the OIC countries have made several strategies to prevent the global recession from getting deeper. Such as Indonesia, which applies a deficit that must be below 3 per cent of GDP in 2023; besides that, Malaysia is increasing the halal industry because the growth of this sector is quite good amidst the world economic crisis. Apart from that, there are Brunei Darussalam, Qatar and Kuwait, which have fundamentals that are strong enough to prevent the global recession from deepening. It is hoped that this research can provide insight to readers about what a global slowdown is and the strategies of OIC member countries.